Promotion of transversal skills through a final degree project - Moya Velasco, Jorge; Torres Polo, Marta (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The aim of this paper is to propose an efficient and integrated model for the selection of personal skills, with the idea of inducing their acquisition among the students in the university. Defined the wide-spectrum skills to be improved, are suggested tools and processes for achieving. In particular, as applied work, the use of the Final Degree Project is offered as a guide to do it. The method consists in allowing the teacher involved in the tutoring of the TFG to choose competences that ensure the transversal learning of the students as well as the motivation of the student in the realization of the project. The results obtained suggest that it is possible through applied programmes such as the one here described to achieve improvements in the skill of the students, while at the same time could improve the final academic results.